2015
DOI: 10.1002/cm.21253
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time imaging of actin filaments in the zebrafish oocyte and embryo

Abstract: Dynamic changes of cytoplasmic and cortical actin filaments drive various cellular and developmental processes. Although real-time imaging of actin filaments in living cells has been developed, imaging of actin filaments in specific cells of living organisms remains limited, particularly for the analysis of gamete formation and early embryonic development. Here, we report the production of transgenic zebrafish expressing the C-terminus of Moesin, an actin filament-binding protein, fused with green fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
(85 reference statements)
1
11
0
Order By: Relevance
“…Zebrafish embryos are amenable to pharmacological treatment by bath application, allowing for treatment of intact, live embryos with compounds known for the modulation of cytoskeletal dynamics, for instance, targeting microtubules: Colchicine (Roche et al, 1994), vinblastine (Keiter et al, 2016; Yao et al, 2017), vincristine (Mizgirev and Revskoy, 2010; Khan et al, 2012; Holloway et al, 2016), nocodazole (Plucińska et al, 2012; Jayachandran et al, 2016) and paclitaxel (Jayachandran et al, 2016). For the actin cytoskeleton: Cytochalasin D (Nukada et al, 2015; Artelt et al, 2018) and latrunculin A (Artelt et al, 2018), jasplakinolide (Artelt et al, 2018), phalloidin oleate (Dutta and Kumar Sinha, 2015), and the inhibitor of actin–myosin interaction BDM (Norden et al, 2009) have been used with success.…”
Section: Advantages Of the Zebrafish Modelmentioning
confidence: 99%
“…Zebrafish embryos are amenable to pharmacological treatment by bath application, allowing for treatment of intact, live embryos with compounds known for the modulation of cytoskeletal dynamics, for instance, targeting microtubules: Colchicine (Roche et al, 1994), vinblastine (Keiter et al, 2016; Yao et al, 2017), vincristine (Mizgirev and Revskoy, 2010; Khan et al, 2012; Holloway et al, 2016), nocodazole (Plucińska et al, 2012; Jayachandran et al, 2016) and paclitaxel (Jayachandran et al, 2016). For the actin cytoskeleton: Cytochalasin D (Nukada et al, 2015; Artelt et al, 2018) and latrunculin A (Artelt et al, 2018), jasplakinolide (Artelt et al, 2018), phalloidin oleate (Dutta and Kumar Sinha, 2015), and the inhibitor of actin–myosin interaction BDM (Norden et al, 2009) have been used with success.…”
Section: Advantages Of the Zebrafish Modelmentioning
confidence: 99%
“…Large numbers of cyclin B1 RNA granules were localized at the animal polar cytoplasm in stage III (Fig. 4d ) and fully grown, stage IV oocytes [ 31 , 32 , 50 ]. The localization and granular structure of dazl mRNA were maintained in stage III and IV oocytes, but the granules were broadly distributed in the vegetal polar cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that zebrafish cyclin B1 mRNA is initially distributed throughout the cytoplasm of oocytes (stages I and II) and becomes localized at the animal polar cytoplasm after stage III, when DIG-labeled RNA probes were recognized by an AP-coupled anti-DIG antibody, followed by detection of signals by precipitation of AP substrates [ 28 ]. Fluorescence in situ hybridization with the TSA system has revealed the localization of cyclin B1 mRNA at the animal polar cytoplasm as RNA granules [ 31 , 32 , 50 ], and this study revealed changes in cyclin B1 mRNA distribution and localization during oocyte development; i.e., cyclin B1 mRNA was initially distributed throughout the cytoplasm of oocytes in stage I and subsequently moved to the animal pole in stage II (Fig. 4a - c ), and a granular structure was first found in stage Ib oocytes and persisted in later stages (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminus of the actin-binding protein, Moesin, has been used in zebrafish to image actin in vivo, through a transgenic line that allows the visualisation of actin filaments and actin dynamics during oogenesis and early development (Nukada et al 2015 ).…”
Section: The Visualisation Of Actin In Cellsmentioning
confidence: 99%
“…The yolk granules are kept at the vegetal pole by means of another actin-based mechanism which is the formation of actin comet-like structures (Shamipour et al 2019 ). Actin dynamics has been studied in oocytes and early embryos using a Moesin-GFP fusion (Nukada et al 2015 ). Germ plasm segregation and localisation of many maternal RNAs in the early embryo have been found to be actin-dependent (Eno and Pelegri 2018 ; Theusch et al 2006 ; Eno et al 2019 ; Nair et al 2013 ).…”
Section: Actin Model Systemsmentioning
confidence: 99%